Deterministic modeling of API5L X52 steel in a coal-tar-coating/cathodic-protection system in soil. (October 2016) - Li, X.M.; Rosas, O.; Castaneda, H.
Abstract: Impedance characteristic signal for a coal tar-coated API5L-X52 steel with cathodic protection has been investigated in soil using electrochemical impedance spectroscopy (EIS). Deterministic transmission line model (TLM) has been set up to simulate the impedance results of pipeline with intact and artificial defect coating, and to verify the damage evolution of coated pipeline with cathodic protection in soil. To illustrate the coating inherent property, coating in each transmission line unit has been assumed to be represent by two imaginary parts: a relatively coating barrier part which serves as parallel of capacitor and resistor (Cper Rper ); and another part considered as porous coating serves as parallel of porous coating and double layer (Cpor Rpor (Cdl Rct )). The parameter θ has been proposed to calculate the total impedance of the coating, to illustrate its performance. An adjustment was applied to calculate total resistance Rt mathematically, based on the simulation results to illustrate the damage evolution concept. The Rt values are in agreement with the proposed damage evolution stages. Highlights: We designed the transmission line model (TLM) for pipeline both with intact coating and artificial defect coating in soil. TLM was applied to study the corrosion damage evolution. Three stages of damage evolution can be detected. The parameter θ and Rt can be used to demonstrate the coating performance and to verify the proposed damage evolution.